The educative role of judo for children in first-cycle primary school: Parents' opinion based on focus group - Aroni, Andre Luis; Machado, Afonso Antonio [UNESP]; Gomes, Antonio Rui; Honorio, Samuel; Santos, Jorge; Batista, Marco (Univ Alicante, 2019)
The recognition of pedagogy and method of Judo was made effective by UNESCO, as a world-wide sport utility in the development of the human being and, as an activity whose spectrum of approach in children's age ranges is quite broad, exerts a preponderant function in the global development of its practitioners, allowing them to transfer the sport context to their specific socio-cultural context. The objective of this study was to relate the practice of Judo in the development of self-concept, self-esteem and academic performance in children's first-cycle primary school. The study group included 8 parents in charge of education, aged 33-45 (M = 39.75 SD = 4.33), 6 female and 2 males, 4 had a bachelor's degree, 2 had an undergraduate degree and two had the 12th grade. According to these parents, the practice of Judo is very much linked to the development of self-concept, emphasizing through the promotion of social acceptance, compliance with rules and responsibility or balanced behaviour. It is also linked to the development of self-esteem, insofar as it is an activity that promotes self-confidence. It also exerts an important influence on school performance, since it promotes concentration. It is also emphasized that in the parents' opinion, the inclusion of Judo in the Physical Education curricular programme would bring several benefits for the integral conception of the child as a citizen.
Keywords: Quantitive analyses; Focus group; Judo; Parents; Sports development